2017
DOI: 10.4103/ijnm.ijnm_28_17
|View full text |Cite
|
Sign up to set email alerts
|

An infrequent case of adult alveolar rhabdomyosarcoma with pancreatic metastases detected in F-18 FDG PET/CT

Abstract: Rhabdomyosarcoma (RMS) is a rare cancer in adults, comprising about 1% of all forms of adult cancer. Common sites of metastases are lungs, skeletal system, lymph nodes, and brain. Metastases of RMS to pancreas are infrequent. We report a case of adult orbital alveolar RMS with pancreatic metastases detected in F-18-fluorodeoxyglucose-positron emission tomography/computed tomography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…CT images allow radiologists not only to determine the extent of tumours but also to determine the absence or presence of bony destruction, calcification, haemorrhage and/or metastases 3 , However, in fact, during the course of routine radiology diagnosis, because RMS has the general radiological appearance of soft tissue tumors, it is difficult to distinguish it from other pelvic soft tissue malignancies. However, to our knowledge, there are currently few literature reports on the CT features of pelvic RMS 4 9 , and some reports have indicated that the CT findings of pelvic RMS lack specificity 10 12 . Therefore, it is imperative to investigate the CT features of pelvic RMS and establish an accurate diagnostic method for pelvic RMS in children.…”
Section: Introductionmentioning
confidence: 99%
“…CT images allow radiologists not only to determine the extent of tumours but also to determine the absence or presence of bony destruction, calcification, haemorrhage and/or metastases 3 , However, in fact, during the course of routine radiology diagnosis, because RMS has the general radiological appearance of soft tissue tumors, it is difficult to distinguish it from other pelvic soft tissue malignancies. However, to our knowledge, there are currently few literature reports on the CT features of pelvic RMS 4 9 , and some reports have indicated that the CT findings of pelvic RMS lack specificity 10 12 . Therefore, it is imperative to investigate the CT features of pelvic RMS and establish an accurate diagnostic method for pelvic RMS in children.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that PET-CT improved the initial staging accuracy in adult RMS, specifically the detection of distant metastatic spread. 6,12,13 In our patient, pancreatic body metastasis was detected by PET-CT.…”
Section: Discussionmentioning
confidence: 57%
“…The pancreas is considered a rare metastatic site in patients with newly diagnosed RMS 6,7 . In a retrospective analysis, four (5.6%) of 77 patients with alveolar RMS had pancreatic metastases at initial presentation, including one adult case, whereas four patients presented with pancreatic metastases at the time of disease recurrence, including one adult case 7 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations